2013
DOI: 10.1103/physrevlett.111.170405
|View full text |Cite
|
Sign up to set email alerts
|

First Experimental Realization of the Dirac Oscillator

Abstract: We present the first experimental microwave realization of the one-dimensional Dirac oscillator, a paradigm in exactly solvable relativistic systems. The experiment relies on a relation of the Dirac oscillator to a corresponding tight-binding system. This tight-binding system is implemented as a microwave system by a chain of coupled dielectric disks, where the coupling is evanescent and can be adjusted appropriately. The resonances of the finite microwave system yield the spectrum of the one-dimensional Dirac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
166
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(169 citation statements)
references
References 41 publications
0
166
0
3
Order By: Relevance
“…Applying the techniques, developed to investigate the band structure of graphene 21,22 and to emulate relativistic systems 46,47 as well as molecular systems 24 , we have performed analogous experiments to study the coherent transport in graphene nanoribbons.…”
Section: A Microwave Experimentsmentioning
confidence: 99%
“…Applying the techniques, developed to investigate the band structure of graphene 21,22 and to emulate relativistic systems 46,47 as well as molecular systems 24 , we have performed analogous experiments to study the coherent transport in graphene nanoribbons.…”
Section: A Microwave Experimentsmentioning
confidence: 99%
“…[3,6]). Recently, the one-dimensional Dirac oscillator has had its first experimental realization [7], which made the system more attractive from the point of view of applications. The Dirac oscillator in (2 + 1) dimensions, when the third spatial coordinate is absent, has also been studied in Refs.…”
mentioning
confidence: 99%
“…Pacheco et al analyzed one-dimensional Dirac oscillator in a thermal bath and they showed that its heat capacity is two times greater than that of the one-dimensional harmonic oscillator for high temperatures [2]. Franco-Villafañe et al performed the first experimental study on one-dimensional Dirac oscillator [3]. Later, Pacheco et al also studied three-dimensional Dirac oscillator in a thermal bath [4].…”
Section: Introductionmentioning
confidence: 99%